The Effect of Gamma Irradiation on Quality of Composite from Bagasse, Bamboo, and Polypropylene Coated Resin - Fatoni, Nur; Ferianto, Muhammad Dzuhri; Rivaldi, Muhammad Ridha; Welerubun, Ignatius Yudha Putra (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Based on data from Direktorat Jenderal Perkebunan the sugarcane production in Indonesia from 2014-2018, sugarcane processing produced bagasse waste with an amount of about 0.825 million tons/year. The data from Badan Pusat Statistik (BPS) showed that national bamboo production in 2014-2018 was above 7 million stems/year. Currently, bagasse waste and bamboo waste are not utilized optimally and have low value. These wastes can be used as composite materials which have a higher economic value. The composite structure can be strengthened by a resin coating and polymerized using gamma irradiation. Gamma irradiation phenomena can also cause degradation which weakens the composite structure, so it is necessary to vary the radiation dose. This research aims to determine the effect of gamma irradiation on composites of bagasse fiber, bamboo fiber, and polypropylene (BBP) on the compressive test, water resistance, and density. BBP composites are made from 10% bagasse fiber, 10% bamboo fiber, and 80% polypropylene with a size of 40 mm x 30 mm x 20 mm. All components were mixed and coated with acrylic resin with a thickness of 2 mm, then irradiated with various doses of 0, 10, 20, 30, 40, and 50 kGy. The results of the BBP composite compressive test for irradiation doses of 0 to 50 kGy were respectively 29.667; 37.167; 50,235; 60,542; 52.537; and 46.545 kg/cm2. The average result of the water-resistance test of the composite BBP absorbs water as much as 0.524 %. The results of the mean density test of the composite BBP obtained 0.894 gr/ml. The strongest composite structure was obtained at a dose of 30 kGy.